Nanoparticle-mediated bioremediation as a powerful weapon in the removal of environmental pollutants. Issue 2 (April 2023) - Chaudhary, Parul; Ahamad, Lukman; Chaudhary, Anuj; Kumar, Govind; Chen, Wen-Juan; Chen, Shaohua
Abstract: Nowadays, contamination due to the organic/inorganic composites has increased promptly due to rising anthropological intrusion which is foremost issue for worldwide food safety and environments. Different physical and chemical approaches have been investigated for the removal of toxic pollutants from the ecosystem. Due to their high costs, ineffective removal methods, toxic material production and large capital requirements have been constrained. Hence it is crucial to develop and achieve environmental sustainability through the use of efficient, environmentally friendly and economically viable approaches. The use of nanoparticles to reduce the contaminants has grown in recent decades. Due to their small size, high reactivity and catalytic activities nanoparticles have been used effectively to remediate the contaminated soil and water. Different microbes such as bacteria, fungi and algal species are also involved in remediation purposes. By immobilizing or stimulating the remediating microbial enzymes, these microbes can act as facilitators in the bioremediation of hazardous substances. Nanoparticles along with microbes have proven to be more efficient than other methods of contaminant removal. Nanobioremediation has enormous potential for large scale environmental clean-up at low cost and with minimal amount of toxic consequences. In this review, we emphasis on the applications of nanoparticles in different sectors and elimination of lethal contaminants such as xenobiotic compounds, synthetic dyes and heavy metals with the help of nanotechnology and microbial inoculants for sustainable development. Graphical Abstract: ga1 Highlights: Nanotechnology has applications in a variety of fields. Nanotechnology is crucial for toxic pollutant removal. Microbial inoculants with nanoparticles remove pollutants more efficiently. Nanoparticle-mediated degradation mechanisms in microbes are discussed.